DEVELOPMENT OF THE JURY TRIAL IN FRANCE - Садовникова, Валерия (SWorldJournal, 2021)
The article considers the main stages of the formation of the jury trial in France, the reasons for its occurrence and its activities in the modern world. The main problems that arose in the process of its creation are revealed.The jury trial today plays